Technical Approaches of PM2.5 Control for Spatial Design in Thailand - Wongwatcharapaiboon, Jitiporn; Riffat, Saffa B. (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
According to PM2.5 situation in Thailand, the monitoring of dust concentration has been exceeding 100 μg/m3 for longer a month period. This level is harmful to all local livings standardized by National Ambient Air Quality standards (NAAQs) and World Health Organization (WHO). However, this problem is specific to location in terms of tropical climate, geographical land, existing policy and people behaviours. Social intervention reviews are separately concerned in another research part of study series. Thus, this paper aims to find suitable PM2.5 purification and techniques matched to tropical climate and high concentration conditions. Environmental factors, probably affect PM2.5 situations, are considered in priority. Systematic reviews of different techniques are literally analysed and synthesized for optimum benefits to local applicants, further research and case studies in teaching class. The results are scoped to three levels of living conditions from outdoor situation for landscape study to architectural integration for architecture study and indoor applicable functions for interior designer study. For outdoor approaches, well connectivity of information in terms of Internet of Things (IoTs) and smart satellite technology are mainly concerned to provide accuracy and reliability, when planting landscape in city is proved to reduce PM2.5. In case of architectural scale, the details of technical and chemical approaches can support physical approaches for design. Lastly, interior scale concerning of air pollution is exemplified for further space design. Suggestions, installations and cautions of applications are perhaps included in each specific session.